Teacher Digital Literacy and Merdeka Curriculum Readiness: The Role of Learning Communities in Preparing 21st-Century Competencies in Secondary Schools - Susy Andriyani; Mohammad Syahidul Haq; Muhamad Sholeh; Mufarihul Hazin; Amrozi Khamidi; Andi Kristanto (Journal of Innovation and Research in Primary Education, 2026)
The global education crisis demands that teachers possess competent digital literacy as a prerequisite for implementing the Merdeka Curriculum and preparing students for 21st-century challenges. However, despite strong policy emphasis on digital literacy and Learning Communities, empirical evidence of their interrelationship in Indonesian secondary school contexts remains limited. This study aims to analyze the effectiveness of Learning Communities as a mechanism for teacher professional development, the level of teacher digital literacy, and the evaluation of the school's digital climate in supporting the synergy between the two. This research uses a descriptive quantitative approach with a cross-sectional survey design, based on data from 39 Junior High School teachers across two work units (SMPN 2 Dawarblandong and SMPN 2 Mojosari). Data were analyzed using descriptive statistics including means, standard deviations, and comparative analysis between schools. The results show that the Learning Community dimension proved highly effective with an average score of 4.78, serving as a core pillar for professional development and teacher self-reflection. The strongest indicator lies in the Learning Communities' ability to help teachers identify strengths and weaknesses in their teaching practices, achieving a score of 4.92. However, the Teacher Digital Literacy dimension recorded the lowest average score of 4.47, with the routine use of Google Classroom as the lowest indicator at 4.23. While leadership support in facilitating Learning Communities is very high at 4.90, formal recognition related to digital innovation by school principals remains moderate at 4.28. It is concluded that Learning Communities have established a strong foundation for collaboration, but there is a significant gap between non-technical collaborative readiness and routine technology adoption. Schools need to reorient Learning Communities to focus on operational technical training and strengthen the recognition system to encourage continuous digital integration in implementing the Merdeka Curriculum.